Dazzled by the strobe lights: Tourist experience and complexity in the night-economy - Christou, Prokopis A.; Pericleous, Katerina; Papatheodorou, Andreas (My University, 2022)
This study that is anchored in complexity theory investigates the complex factors affecting the destination nightlife experience of tourists while using the destination of Cyprus as a fitting place context. Based on a sample of 390 holidaymakers, a fuzzy-set Qualitative Comparative Analysis reveals certain complex solutions. These deal with the social and marketing nexus; the socio-cultural and quality connection; and the relationship between price with quality in the night economy. In spite of hygiene and safety issues that are deemed necessary for the prevention of a non-positive overall night-time experience, the socializing aspect is the one that appears to prevail within the nightlife tourist experiential milieu.
Keywords: Complexity theory; Cyprus; fsQCA; Night economy; Tourist experience